RATIONING LIQUID WASTES - Дегтярь, Мария (SWorldJournal, 2021)
The actual problem of liquid household waste management and peculiarities of their rationing has been considered, the peculiarities of accounting of volumes of water supply and drainage and comparison of normative volumes and actual ones are shown. A num